CHALLENGES IN THE TRAINING OF LIBRARIANS ON INFORMATION AND COMMUNICATION TECHNOLOGY IN FESTUS AGHAGBO NWAKO LIBRARY, NNAMDI AZIKIWE UNIVERSITY, AWKA - Ezejiofor, Obianuju Victoria (NAU Journal of Library and Information Science, 2018)
The paper sought to investigate challenges facing Festus Aghagbo Nwako Library and the librarians in ICT training. Data was collected through observation and interview methods. The population of the study is made up of all the librarians in the library. The major challenges discovered were insufficient fund, inadequate number of professional librarians, inadequate facilities, lack of written policy on training and non-sustenance of training programmes.